hello slove this. !!!!!
ANSWEr nhI aata to.mat Dena Varna I'd delete !!
Attachments:
![](https://hi-static.z-dn.net/files/de1/7e8e87cf518fb19f07f27e84a3c5dd63.jpg)
Answers
Answered by
7
1) ->
-
,
->
-
=>I x -x 0 I
I 0 x -x I = 0
I a b x+c I
=>->
+
,
->
+
=>I 0 -x 0 I
I x 0 -x I = 0
I a+b x+b+c x+c I
=> -(-x) (+xc+ax+bx)=0......1stequation
So by this equation.......
=> (x=0) , +x(a+b+c)=0
x(x+a+b+c)=0 .........2th equation
We already have x = 0
So from 2nd equation we get.....
=>x= -(a+b+c)
Ans is ......x= -(a+b+c) and x = 0
Similar questions